An empirical analysis of the relationship between Board and Committee activities and Bank Risk - Ioannou, Kyriaki (2017)
After the consequences of the 2007 Global Financial crisis, board and committees are working harder but are they really adding value to the bank? This analysis finds evidence on the corporate governance structure of U.S holding banks over the period of 1999 until 2014. To investigate the relationship between board and committee activities and bank risk, this study uses board and committee activity as meeting frequency component and meeting fees and annual retainer as the compensation component. The committees analysed are Audit, Compensation, Nominating and Governance and Risk committees and the board of directors. The results of examining the impact of compensation structure on meeting frequency is a negative association between meeting fees and meeting frequency but a positive association between annual retainer and meeting frequency. Further, to analyse the impact on bank risk we are using board and committee activity and conclude that bank risk is negatively affected by meeting frequency. The impact on bank performance is also examined in order to understand whether the meetings held add value to the bank. The main focus of this study is how bank risk can be reduced by controlling the board’s and committees’ activity. The inclusion of Risk committee is a unique and unseen feature in the analysis which is considered among the other main standing committees of the board to produce a robust outcome. Tobin’s Q is used to regress bank performance and Risk-weighted assets to regress bank risk which are found to be strongly correlated but collinearity issue is fixed throughout the analysis. The analysis emphasises on how the activity of the board and its standing committees influence bank risk by introducing compensation variables.